2007
DOI: 10.1007/s10681-007-9363-0
|View full text |Cite
|
Sign up to set email alerts
|

The use of wild relatives in crop improvement: a survey of developments over the last 20 years

Abstract: The use of crop wild relatives (CWR) genes to improve crop performance is well established with important examples dating back more than 60 years. In this paper, we review available information on the presence of genes from CWR in released cultivars of 16 mandate crops of the CGIAR institutes, and some selected additional crops, focusing on the past 20 years-the period since a comprehensive review by Robert and Christine Prescott-Allen in 1986. It appears that there has been a steady increase in the rate of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
634
1
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 903 publications
(648 citation statements)
references
References 47 publications
4
634
1
9
Order By: Relevance
“…Plant breeders exploit this wild diversity through a variety of traditional and modern genomic means, but generally seek to enhance or restore adaptive traits lost or degraded over the course of crop domestication. Commonly targeted genes and traits include those which underpin crop resistance to pests and disease, but have also included abiotic stress, yield and quality related traits (Dwivedi et al., 2008; Hajjar & Hodgkin, 2007; Maxted & Kell, 2009; Vincent et al., 2013). Such exploitation of CWRs in crop improvement programmes has grown steadily since the middle of the last century (Heywood, Casas, Ford‐Lloyd, Kell, & Maxted, 2007; Maxted & Kell, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant breeders exploit this wild diversity through a variety of traditional and modern genomic means, but generally seek to enhance or restore adaptive traits lost or degraded over the course of crop domestication. Commonly targeted genes and traits include those which underpin crop resistance to pests and disease, but have also included abiotic stress, yield and quality related traits (Dwivedi et al., 2008; Hajjar & Hodgkin, 2007; Maxted & Kell, 2009; Vincent et al., 2013). Such exploitation of CWRs in crop improvement programmes has grown steadily since the middle of the last century (Heywood, Casas, Ford‐Lloyd, Kell, & Maxted, 2007; Maxted & Kell, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it has previously been estimated that about 30% of gains in crop yield worldwide—corresponding to an annual value of US $151 billion—could be attributed to the incorporated use of CWR germplasm (Pimentel et al., 1997). Furthermore, the frequency of release of cultivars containing CWR genes is set to further increase into the future (Dempewolf et al., 2017; Hajjar & Hodgkin, 2007; Lane & Jarvis, 2007), highlighting the renewed role for research in helping to meet this demand.…”
Section: Introductionmentioning
confidence: 99%
“…Gene flow between wild and cultivated types is an important element of crop adaptation in their centres of origin (e.g. Rodríguez et al 2010;Hufford et al 2013;Mutegi et al 2015), and the role of crop wild relatives as a source of stress tolerance and resistance traits for crop breeding is well acknowledged (Hajjar and Hodgkin 2007;Jansky et al 2013). This study also revealed the value of hardy wild relatives of quinoa, cañahua, and potato as famine foods for Altiplano communities in periods of climate stress.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, their inherent yield potential is low as compared to other pulses and requires to be enhanced thorough recombination breeding. Efforts have been made to search for genes imparting yield traits and resistance to biotic and abiotic stresses within the cultivated species and to a limited extent among their wild relatives but success has been limited to a few diseases and insect pests; mostly where the genes are confined to the primary gene pool of the particular species (Knott and Dvorak, 1976;Stalker 1980;Ladizinsky et al, 1988;Prescott and Prescott, 1986;Kumar et al, 2003;Hajjar and Hodgkin 2007). The use of wild relatives as sources of new germplasm is well established in crop breeding programs in several crops, especially cereals, but the efficiency with which wild germplasm is utilized for introducing disease resistance and other agronomic characters into elite cultivars varies greatly from species to species (Bisht et al, 2005a(Bisht et al, , 2005bKumar et al, 2011).…”
Section: Introductionmentioning
confidence: 99%